INDIAN SOFTWARE INDUSTRY: CURRENT ISSUE AND FUTURE PROSPECTS - Grace Varghese (ISDA Journal, 2013)
The IT and IT enabled services (ITeS) industries in India have become highly visible nodes of the global economy, attracting substantial business interests as a prime destination for outsourcing and off-shoring. IT has come to be regarded as a model for India’s future economic growth and development. This paper attempts to examine the emerging challenges of Indian Software Industry and tries to assess its future prospects. The researcher recognizes that IT industry is distinctive in that it is catering to the global market, and often affected by the policies of consumer countries. India is one of the largest exporters of software, but many of its infrastructure and business practices are widely seen as being quite primitive. The study also tries to identify a few advantages and disadvantages of the industry in India. Indian IT industry, so far, tells the success story and has largely contributed to the economic progress; on the other hand, tough competition is expected to increase and salary growth gets slower, which casts shadows over its bright future.